The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Day 3 Thu, November 19, 2020 2020
DOI: 10.2118/202363-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Injection for Improved Recovery in Tight Gas Condensate Reservoirs

Abstract: Condensate banking is one of the main challenges facing operators of gas condensate reservoirs. Different techniques have been used over the years to improve well deliverability in condensate reservoirs, including gas recycling, gas injection, matrix acidization and hydraulic fracturing. This study investigates design options for effective CO2 injection strategies to reduce liquid blockage and improve productivity in tight reservoirs. We use dynamic compositional models to simulate condensate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Different gas injection methods have different effects on EGR in condensate gas reservoirs with different permeability capacity. El Morsy et al [76] constructed an ideal reservoir model, focusing on tight condensate gas reservoirs, and set 0.1 mD and 1 mD permeability reservoirs for continuous gas injection, and huff and puff gas injection, respectively, for comparison. The analysis concluded that CO 2 huff and puff gas injection is better for tight condensate gas reservoirs and continuous gas injection is better for condensate gas reservoirs with better permeability.…”
Section: Condensate Gas Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different gas injection methods have different effects on EGR in condensate gas reservoirs with different permeability capacity. El Morsy et al [76] constructed an ideal reservoir model, focusing on tight condensate gas reservoirs, and set 0.1 mD and 1 mD permeability reservoirs for continuous gas injection, and huff and puff gas injection, respectively, for comparison. The analysis concluded that CO 2 huff and puff gas injection is better for tight condensate gas reservoirs and continuous gas injection is better for condensate gas reservoirs with better permeability.…”
Section: Condensate Gas Reservoirsmentioning
confidence: 99%
“…This shows that in conventional gas reservoirs, gas injection is mainly used to drive and sweep natural gas, and there are also errors that do not take into account mixing and solubility. El Morsy et al [76] studied the effect of mixed gas on enhanced gas recovery and revealed that the effect of mixture gas injection in tight condensate gas reservoirs was not much different from that of pure CO 2 , which would be more economical but would have an impact on condensate gas production, because N 2 would reduce the minimum miscible pressure of CO 2 .…”
Section: Research On the Influence Of Reservoir Physical Properties A...mentioning
confidence: 99%
“…But the experiments are all at the core scale and have certain limitations. Some scholars have also conducted numerical simulations of CO 2 injection into condensate gas reservoirs [59]. The results show that compared to continuous injection of CO 2 , CO 2 -HnP can improve condensate oil recovery to 25%, which is much higher than with the continuous injection of CO 2 [60].…”
Section: Introductionmentioning
confidence: 99%